Shielding Effectiveness of Laminated Shields - Jayasree, P. V. Y.; Baba, V. S. S. N. Srinivasa; Rao, B. Prabhakara (Společnost pro radioelektronické inženýrství, 2008)
Shielding prevents coupling of undesired radiated electromagnetic energy into equipment otherwise susceptible to it. In view of this, some studies on shielding effectiveness of laminated shields with conductors and conductive polymers using plane-wave theory are carried out in this paper. The plane wave shielding effectiveness of new combination of these materials is evaluated as a function of frequency and thickness of material. Conductivity of the polymers, measured in previous investigations by the cavity perturbation technique, is used to compute the overall reflection and transmission coefficients of single and multiple layers of the polymers. With recent advances in synthesizing stable highly conductive polymers these lightweight mechanically strong materials appear to be viable alternatives to metals for EM1 shielding.
Keywords: Laminated shield; shielding effectiveness; frequency; conductive polymer